2004
DOI: 10.1093/aob/mch122
|View full text |Cite
|
Sign up to set email alerts
|

Night Temperature has a Minimal Effect on Respiration and Growth in Rapidly Growing Plants

Abstract: These findings indicate that whole-plant respiration of rapidly growing plants has a small sensitivity to temperature, and that the sensitivity does not change among the species tested, even after 20 d of treatment. Finally, the results support respiration models that separate respiration into growth and maintenance components.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
62
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(70 citation statements)
references
References 56 publications
7
62
0
1
Order By: Relevance
“…It is likely that high temperature plus CO 2 enrichment conditions increase the accumulation of stem photoassimilates, as observed in the CG7484RR cultivar (Figure 6). Frantz et al (2004) found an increase of 4.0%/°C in the plant respiration in soybean, along with decrease in leaf and root biomass with reduction in the carbon fraction of the leaves; while stem biomass increased significantly without alteration in carbon fraction.…”
Section: Dry Matter Plant Partitioning and Soybean Yieldmentioning
confidence: 85%
See 1 more Smart Citation
“…It is likely that high temperature plus CO 2 enrichment conditions increase the accumulation of stem photoassimilates, as observed in the CG7484RR cultivar (Figure 6). Frantz et al (2004) found an increase of 4.0%/°C in the plant respiration in soybean, along with decrease in leaf and root biomass with reduction in the carbon fraction of the leaves; while stem biomass increased significantly without alteration in carbon fraction.…”
Section: Dry Matter Plant Partitioning and Soybean Yieldmentioning
confidence: 85%
“…The day/night temperatures in T2 and T3 can be explained by the energy partitioning and balance, deriving of the heat accumulation on soil, vegetative tissues respiration, and lower air movement. The condition of higher mean temperatures could increase day/night respiration and the carbon use (Frantz et al, 2004). It has also been shown that soybean grown under high [CO 2 ] experiences leaf respiration increase by a factor of 2.5 when the night average temperature increases between 18 and 26 °C (Bunce, 2005).…”
Section: Meteorological Conditionsmentioning
confidence: 99%
“…In previous studies examining the effects of night warming on plant growth (Wan et al 2009;Frantz et al 2004;Clark et al 2003;Cheesman and Winter 2013), both negative effects of night warming on tropical tree performance (Clark et al 2003) and positive effects of elevated night temperature on seedlings of two neo-tropical tree species (Cheesman and Winter 2013) have been reported. In the present study, night warming significantly suppressed the growth and development of M. truncatula.…”
Section: Discussionmentioning
confidence: 99%
“…Growth respiration is typically much less sensitive to warming than maintenance respiration (Frantz et al, 2004), and we therefore do not consider a temperature dependence of this particular respiration term.…”
Section: Temperature Responsementioning
confidence: 99%